The surrogate motherhood in assisted human reproduction - Arévalo Martos, Carmen Rocío (2022)
In this article, the author discusses the legal problems of surrogate motherhood in assisted human reproduction. Thus, she evidences the insufficiency of Peruvian regulations to face this reality allowed by biotechnology. In this regard, she analyzes the regulations on the subject, as well as some cassation judgments of the Supreme Court of Justice and the legislative initiatives presented in the Congress of the Republic on surrogate motherhood.